Analisis Pengamanan Pagar Perimeter Dalam Menunjang Keamanan Penerbangan di Bandar Udara Internasional Adi Soemarmo - Astawa, Kadek Oka Putra; Puspitasari, Yulia Aji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The way that airports are able to protect aircraft that will take off and Landing from various disturbances that could endanger flights at the airport is by carrying out perimeter fences and being guarded by aviation security personnel. Therefore, the purpose of this study is to analyze how security is carried out by aviation security personnel on the perimeter fence in supporting flight security at Adi Soemarmo International Airport. In addition, this study also aims to determine whether the security of the perimeter fence is effective in supporting aviation security at Adi Soemarmo International Airport. This research is a qualitative research using primary and secondary data types. The data collection technique in this study uses the method of interviews with Aviation Security personnel, observation during patrols around the perimeter fence area, and documents in the form of documentation when conducting research. The results of this research indicate that the perimeter fence security carried out by Aviation Security personnel at Adi Soemarmo International Airport is in accordance with applicable procedures or provisions and is effective in supporting flight security. Although there are still some shortcomings, the Aviation Security unit at Adi Soemarmo International Airport can cover these weaknesses in accordance with the Regulation of the Indonesian Minister of Transportation Number PM 33 of 2015, by conducting additional mitigation.